Book Sharing: Parentsâ Read Aloud Activities in Supporting Emergent Reading and Arts for Early Literacy - Chasanatun, Fida; Susari, Hermawati Dwi; *, Sunardi; Nurkamto, Joko; *, Asrowi (Proceeding of International Conference on Teacher Training and Education, 2016)
The golden age is an important period when children receive a wide range of knowledge. It takes place between two years of age to six. The initial process of early literacy starts also here in which several components state meaningful supports; vocabulary, print knowledge, phonological awareness, emergent reading, and arts. Three previous studies for this article show that the integration between learning at home and at school for the supports is not yet integrated. Based on the research results that are relevant to this study, it was found that children whose parent were optimizing the chance of receiving a stimulus language well, will grow into adults who are capable in terms of language as well as having a tendency to more easily understand the readings five times greater than adults who in his childhood did not receive the same stimuli. The general objective of this study was to find the concept of activity-based meaningful language activities either through sub reading, storytelling, dialogue, as well as arts of toddlers. The specific objective of this study was to: Discover how the existing conditions in similar processes and guidelines that are applied in other countries as a comparison; Finding the design and guidelines for teacher and parent in facilitating emergent reading and arts; Finding the effectiveness of on-going literacy learning activities. Mix methods applied here took 40 teachers and 40 parents lived in Madiun and surroundings. The first questionnaire and observation for both participants showed what real emergent and arts activities for their children and also whether those acts were standardized or not. The second part was sharing the program and figuring the guidelines which lead them act as the target shared. And the last one was the evaluation which promoted observation, interviews and documents from the progress.